The moral obligation to include pregnant women in clinical trials - Ramtahal, Kieara-Lee (University of the Witwatersrand, Johannesburg, 2024)
Many pregnancies are complicated by serious medical conditions that require treatment, and despite the need to use medication during pregnancy, the majority of clinical trials do not include the pregnant population, which leaves pregnant women with limited “robust” data regarding the safety and effectiveness of medications that they may require during pregnancy (Little & Wickremsinhe, 2017, p.1). In this report, I examine the reasons provided for the exclusion of pregnant women from clinical trials and the ethical reasons for their inclusion. I argue that, 1. the exclusion of pregnant women as participants in clinical trials could potentially expose future pregnant women to significant harms, 2. the benefits arising out of the inclusion of pregnant women in clinical trials far exceeds the possible harms to the pregnant women trial participants and their fetuses and 3. pregnant women deserve fair access to research trials where their participation will involve access to potential benefits. I also discuss objections to my arguments and provide a response. In conclusion, I contend that pregnant women should be included in clinical trials unless there are compelling reasons for exclusion.
A research report submitted in partial fulfillment of the requirements for the degree of MSc (Med) in Bioethics and Health Law to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: Moral obligation; Pregnant women; Clinical trails; UCTD; SDG-3: Good health and well-being